LAND REGULARIZATION, SOCIAL FUNCTION OF PROPERTY, AND METHODOLOGICAL APPROACHES FOR THE ANALYSIS OF SPECIAL RURAL ADVERSE POSSESSION IN THE DISTRICT OF MONTES CLAROS/MG - Tiago, Josiellen Cristhian da Silva; Augusto, Helder dos Anjos (Seven Editora, 2025)
This article examines the theoretical foundations and methodological procedures adopted in the analysis of special rural adverse possession in the District of Montes Claros/MG, with an emphasis on verifying its effectiveness as an instrument for realizing the social function of land. Based on a historical understanding of Brazilian land formation and the constitutional framework that governs the productive and responsible use of land, the study points to a methodology that includes legal references, documentary analysis, and geoprocessing techniques to identify, systematize, and evaluate the effectiveness of the social function of rural properties susceptible to special rural adverse possession, notably in the district of Montes Claros/MG. The methodology developed involves three main stages: bibliographic and regulatory review; collection and examination of registry and judicial documents produced by the district’s registry offices; and spatial analysis of the selected areas using MapBiomas geographic databases integrated with QGIS software. This interdisciplinary approach allows not only for an understanding of the legal history of the institution, but also for the mapping, description, and interpretation of the territorial dynamics linked to possessions qualified by residence and family productivity. By proposing a replicable methodological model, the article contributes to the improvement of academic research on land regularization, land use, and rural development, providing support for the empirical evaluation of the social function of property in specific regional contexts. DOI: https://doi.org/10.56238/sevened2025.036-122